MEDIA ALTERNATIVE PERBANYAKAN IN-VITRO ANGGREK BULAN (Phalaenopsis amabilis) - Kasutjianingati, Kasutjianingati; Irawan, Rudi (Jurnal Agroteknos, 2013)
The aim of this research was to study the effects of alternative medium composition on micropropagation of Phalaenopsis amabilis. The species is one of the most important “queen of flower“commodities in Indonesia and it can increase domestic incomes. Completely randomized design was used for the experiment. The experiment used a single factor, multiplication media, consisted of 6 different compositions, i.e. VW + BAP 2 ppm, VW+ coconut water 150 ml/L, VW + Ambon banana extract 50 gt/L, POY + BAP 2 ppm, POY+ coconut water 150 ml/L, POY + Ambon banana extract 50 gt/L . Parameters observed were the number of shoots, leaves and roots. The results showed that addition of coconut water, banana extract, and BAP on media VW (Vacin and Went) or POY (liquid organic fertilizer Yoga) were not significantly different. Shoot number obtained was as many as 2 shoots. Key words: coconut water , banana extract, liquid organic fertilizer, Phalaenopsis